Does Parallel Projection is Suitable in Electrical Capacitance Tomography? –A Comparison with Common Approach - Muhammad Faris Aiman, Hisham; Yasmin, Abdul Wahab; Zainah, Md. Zain; Nurhafizah, Abu Talip; Rohana, Abdul Karim; Nor Farizan, Zakaria; Nurul Wahidah, Arshad (Malaysian Society for Computed Tomography and Imaging (MyCT), 2021)
Electrical Capacitance Tomography (ECT) is one of the soft field tomography that widely used for the purpose of measurement and monitoring of multiphase flow. Common problem of the soft field tomography is low quality and unstable images in the pipe especially at the center section of the pipe. In this paper, an ECT system with a comparison between common approach and a parallel approach is presented. Simulation in 2 dimensions with 16-electrode is carried out to observe a potential projection. The COMSOL Multiphysics software is used to investigate the state and response of the electric field with this approach by exporting data with 128x128 pixels. Air bubbles as a phantom in the oil medium have been tested and analyzed. Linear Back-Projection Algorithm (LBP) is implemented using MATLAB software to obtain a tomogram. A Multi Scale Structural Similarity, MSSIM was applied to compare both approaches. Consequently, the resolution and quality of the pictures in the pipes can be distinguished. However, a further investigation is needed to improve the parallel approach for ECT system.